Melanin-Concentrating Hormone and Sleep Molecular, Functional and Clinical Aspects (Springer International Publishing, 2018)
This book offers a compilation of papers on the role of melanin-concentrating hormone (MCH) in sleep, sleep disorders and neuroendocrine functions. Leading experts in sleep medicine, psychiatry and neuroendocrinology provide a broad perspective on the field, from the anatomical structure and physiology of the MCH system to the connection with other systems influencing sleep and diseases like anxiety and depression. The potential of MCHR-1 antagonists as anxiolytic/antidepressant drugs is also reviewed. The book will represent an interdisciplinary guide for sleep disorder specialists, sleep researchers, psychiatrists, neurologists, psychologists, and behavioral sleep medicine specialists. .